Representasi Kekerasan dalam Webseries Katarsis Season 1 - Rifqi Waluya; Baksin, Askurifai (UNISBA Press, 2024)
Abstract. In this research, the researcher raises the formulation of the problem, namely how physical violence is represented in the Webseries Katharsis season 1. This research aims to reveal the issue of violent scenes contained in the film in a comprehensive and in-depth manner . This research uses a qualitative research method with Christian Metz's semiotic analysis approach. This type of research aims to determine the attitude depiction of each scene of violence in the webseries Katharsis season 1. Then the data is analyzed using Metz's 8 mapping steps from The Large Syntagmatic Analysis in Christian Metz's theory . This 48 minute webseries is divided into 5 violent segments containing 4 elements of the Christian Metz syntagma. The syntagmas contained are, Scene, Subjective Insert, Ordinary Sequence, and Explanatory Insert. The violence displayed is verbal, non-verbal and symbolic violence. Verbal violence occurs through insults and curses, non-verbal violence occurs through stabbing and beating, symbolic violence is presented through psychological manipulation by the actors. Researchers analyze the factors that cause violence that occurs in web series, such as environmental conditions and mental health as triggers for violence. Abstrak. Dalam penelitian ini, peneliti mengangkat rumusan masalah yaitu bagaimana representasi kekerasan fisik dalam Webseries Katarsis season 1. Penelitian ini bertujuan untuk mengungkap persoalan adegan kekerasan yang terkandung di dalam film tersebut secara menyeluruh dan mendalam. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan analisis semiotika Christian Metz, jenis penelitian ini bertujuan untuk mengetahui penggambaran sikap dari setiap scene adegan kekerasan dalam webseries Katarsis season 1. Kemudian data tersebut dianalisis dengan 8 langkah pemetaan Metz dari Analisis The Large Syntagmatic dalam teori Christian Metz. Webseries berdurasi 48 menit ini terbagi ke dalam 5 segmen kekerasan yang mengandung 4 unsur syntagma Christian Metz. Adapun syntagma yang terkandung yaitu, Scene, Subjective Insert, Ordinary Sequence, dan Explanatory Insert. Kekerasan yang ditampilkan yaitu kekerasan verbal, non-verbal, dan simbolik. Kekerasan verbal muncul lewat hinaan dan makian, kekerasan non-verbal terjadi melalui penikaman dan pemukulan, kekerasan simbolik dihadirkan lewat manipulasi psikologis oleh pemerannya. Peneliti menganalisis faktor-faktor penyebab kekerasan yang terjadi dalam webseries, seperti kondisi lingkungan dan kesehatan mental sebagai pemicu kekerasan.